Occupational Migration Out of Agriculture: A Cross-Country Analysis - Mundlak, Yair (The Review of Economics and Statistics, 1978)
AS is well known, economic growth leads, not without a feedback, to changes in the industrial composition of the economy. The seminal work of Simon Kuznets (1966, 1971) has well quantified various aspects of this process. One such aspect, which is of immediate interest to this paper, is the continuous decline in the relative importance of agriculture, a phenomenon that has already been observed by Engel (1857).' A change in industrial composition takes place through a change in resource allocation, including labor, leading to what can be referred to as occupational migration. Part of this phenomenon involves actual change of occupation by workers and part is performed by new entrants into the labor force whose choice of occupation differs from that of veteran workers. The relative importance of these two components may depend to a large extent on the rate at which the economy changes its composition as compared with the natural rate of population (labor force) growth. Independently of the form, at any point in time, the existing opportunities presumably dictate the allocation, and the more attractive the new opportunities are, the more people will be attracted. It is this premise, almost axiomatic to economists, that this paper proposes to measure. It is clear that the question of sectoral migration is of prime importance and that it bears important policy implications as well as having an analytic role. However, in spite of the importance of the subject, there does not seem to be any empirical sectoral migration equation at the macro level.2 The reason is not clear. It is possible that aggregation blurs the data and makes it difficult to obtain acceptable estimates. Whether or not this is the reason, it is clear that if such an equation is important, the data should reveal it and there must be a way to estimate it. In such an undertaking, it helps to have data with a large spread in the important variables. Such data are provided by a cross-section of countries. The plan of the paper is as follows. Section II deals with the formulation of the problem. It relies on existing and known concepts and it therefore concentrates on bringing the concepts together for the purpose at hand. Section III presents the results. A few concluding remarks appear in section IV.